Study of Criminology Juvenile Justice in Icoaraci District - Belém- PA - Joao Paulo Carneiro Goncalves Ledo (Revista de Criminologias e Politicas Criminais, 2016)
Field Research about juvenile criminal program put into practice in Icoaraci District, belongs the city of Belém, Pará State. As inspiration has one Vera Malaguti Batista research (2013 ). Making a historical approach. Reflects in practice the doctrine of integral protection can have character of reversibility because mechanisms apparently aimed at the satisfaction of human rights in your concrete action, trigger can own violation of human rights. Shows the data collected and ends with a critical approach about selectivity and violation of rights.